Evaluating the Sustainability of Wheat–Maize System with a Long-Term Fertilization Experiment - Yun Shao; Jiahui An; Xueping Wang; Shouchen Ma; Ye Meng; Yang Gao; Shoutian Ma (Agronomy)
In light of the issue concerning excessive fertilization that prevails in the Huang-Huai-Hai Plain, through conducting a 13-year long-term positioning experiment, the sustainability of a wheat and maize double-cropping soil system under different fertilization strategies is evaluated using the triangular area method. The objective is to establish a theoretical basis for the development and implementation of appropriate fertilization practices in the Huang-Huai-Hai Plain. In the protracted long-term experiment, chemical fertilizer (F) was taken as the control (CK) and three distinct treatments combining organic and inorganic fertilizers were used: chemical fertilizer with straw mulching (FS), chemical fertilizer with cow dung (FM), and chemical fertilizer with cow dung and straw mulching (FMS). Between 2018 and 2019, a non-fertilization treatment was concurrently incorporated in parallel on the foundation of each existing fertilization treatment. The results indicated that following prolonged fertilization, the soil nutrient content, enzyme activity, and crop yield of each organic fertilizer treatment were significantly greater than those of the chemical fertilizer treatment alone, resulting in a more stable yield. After two years of discontinuation of fertilizer cultivation, the soil fertility indexes of each treatment exhibited a notable decline. However, the rate of decrease in soil fertility indexes for the three organic fertilizer treatments was lower compared to that of the single application of chemical fertilizer treatment, suggesting that long-term allocation of organic + inorganic fertilizers contributes to better preservation of soil fertility. Through an assessment of the soil system’s sustainability under various treatments, it becomes evident that following a two-year cessation of fertilization, the sustainability indexes of the soils subjected to three long-term organic + inorganic fertilizer treatments (1.26, 1.29, and 1.27) exceeded that of the soil treated solely with chemical fertilizer (1.00). These findings provide further evidence supporting the notion that the combined application of organic and inorganic fertilizers can enhance the soil system’s capacity for sustainable production in wheat–maize farmland within the Huang-Huai-Hai Plain.